A Novel Single Nucleotide Polymorphism in Exon 4 of Insulin-Like Growth Factor-1 Associated with Production Traits in Bali Cattle - . Maskur; C Arman; C Sumantri; E Gurnadi; . Muladno (Faculty of Animal Science, Bogor Agricultural University, 2012)
Insulin-like growth factor-1 (IGF-1) is one of the gene candidates that can be used in selection strategy by using DNA markers (marker assisted selection). Gene candidate strategy is a molecular biology techniques to identify quantitative trait loci directly, with the assumption that genetic variation associated to quantitative trait variation. This study was designed to identify any new mutations in exon 4 that can cause the IGF-1 gene polymorphism and then affect the production traits on Bali cattle. Single nucleotide polymorphism (SNP) discovery was conducted by using the direct sequencing technique. Genetic variation of the genes candidate was identified by using PCR-RFLP technique. The results of this study indicate the presence of a new SNP in exon 4 of IGF-1 gene caused by the T/C transition, which can be identified using Rsa1 restriction enzyme. Genotypic polymorphism of IGF-1/Rsa1 has a significant influence on birth weight, weaning weight and average daily gain of Bali cattle. CC genotype had a birth weight rate, weaning weight and average daily gain of: 15.64±1.83; 83.15±9.00, and 0.439±0.07 respectively, higher than the TT and CT genotype. IGF-1/Rsa1 can be used as a genetic marker for selection of birth weight, weaning weight, and daily body weight gain.